Exogenous brassinolide improves the antioxidant capacity of Pinellia ternata by enhancing the enzymatic and nonenzymatic defense systems under non-stress conditions - Guo, Chenchen; Chen, Ying; Wang, Mengyue; Du, Yu; Wu, Dengyun; Chu, Jianzhou; Yao, Xiaoqin (Frontiers in Plant Science, 2022)
Brassinolide (BR) improves the antioxidant capacity of plants under various abiotic stresses. However, it is not clear about the effect of BR on the antioxidant capacity in plants under non-stress conditions. In the present study, the antioxidant defense response of P. ternata was to assessed by applying BR and propiconazole (Pcz) under non-stress conditions. BR treatment enhanced the flavonoid content, peroxidase, and ascorbate peroxidase (APX) activity by 12.31, 30.62, and 25.08% and led to an increase in DPPH radical scavenging activity by 4.31% and a decrease in malondialdehyde content by 1.04%. Exogenous application of BR improved the expression levels of PAL, CHS, CHI, and DFR genes by 3.18-, 3.39-, 2.21-, and 0.87-fold in flavonoid biosynthesis, PGI, PMI, and GME genes by 6.60-, 1437.79-, and 3.11-fold in ascorbic acid (ASA), biosynthesis, and γECs and GSHS genes by 6.08- and 2.61-fold in glutathione (GSH) biosynthesis pathway, and the expression of these genes were inhibited by Pcz treatment. In addition, BR treatment promoted the ASA-GSH cycle by enhancing the expression of APX, DHAR, and MDHAR genes, which were enhanced by 3.33-, 157.85-, and 154.91-fold, respectively. These results provided novel insights into the effect of BR on the antioxidant capacity in bulbil of P. ternata under non-stress conditions and useful knowledge of applying BR to enhance the antioxidant capacity of plants.